PENERAPAN METODE FIFO DAN FEFO DALAM PENGELOLAAN GUDANG FARMASI PT RAJAWALI NUSINDO CABANG MADIUN - Sari, Alena Puja; Priyanto, Priyanto (Politeknik Negeri Madiun, 2024)
Warehouses are crucial in the business of trading goods. Warehouse management is very important for business sustainability, because the warehouse is directly related to sales activities. The pharmaceutical warehouse of PT Rajawali Nusindo Madiun requires proper, effective and efficient as well as sustainable management in order to keep goods safe and of good quality. This study aims to describe warehouse management using the FIFO FEFO method at PT Rajawali Nusindo Madiun branch. The indicators used include receipt of goods, storage of goods, maintenance of goods, distribution of goods, and administration. The results of this study show that warehouse management has implemented the FIFO FEFO method in the aspects of receipt, storage, maintenance, distribution of goods, and administration.